2012
DOI: 10.1093/geront/gns155
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviors of Older African Americans: An Application of the Theory of Planned Behavior

Abstract: Results indicated that the theory of planned behavior can be used to explain variation in older African Americans' eating behavior. This study also emphasizes the value of considering broader behavioral domains when employing the theory of planned behavior rather than focusing on specific behaviors. Furthermore, social service programs aimed at reducing the incidence of diseases commonly associated with poor eating behaviors among older African Americans must consider promoting not only fruit and vegetable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
3
22
1
Order By: Relevance
“…Although this is in contrast to the results of several studies that did find TPB support when examining somewhat similar samples as the current study’s, as noted in the Introduction, several of these prior findings require qualification due to factors such as limited generalizability, measurement issues, or having accounted for only small amounts of variance (Conner et al, 2002; Gardner & Hausenblas, 2004; Gatt & Sammut, 2008; Godin et al, 2010; O’Neal et al, 2014). Additionally, the current study controlled for baseline behavior (McEachan et al, 2011), in an effort to determine the TPB’s contribution to predicting future dieting above and beyond what typically can be predicted simply from knowing an individual’s past eating behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although this is in contrast to the results of several studies that did find TPB support when examining somewhat similar samples as the current study’s, as noted in the Introduction, several of these prior findings require qualification due to factors such as limited generalizability, measurement issues, or having accounted for only small amounts of variance (Conner et al, 2002; Gardner & Hausenblas, 2004; Gatt & Sammut, 2008; Godin et al, 2010; O’Neal et al, 2014). Additionally, the current study controlled for baseline behavior (McEachan et al, 2011), in an effort to determine the TPB’s contribution to predicting future dieting above and beyond what typically can be predicted simply from knowing an individual’s past eating behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the studies included other self-care behaviors, such as glucose monitoring and medication management (diabetes) (Didarloo et al, 2012; Gatt & Sammut, 2008), thereby making it difficult to tease out the healthy eating component. In a separate study, the TPB predicted increased fruit/vegetable consumption for older African Americans who were participating in a cardiovascular risk-reduction project (O’Neal et al, 2014). Another study discovered that the TPB predicted healthy eating intentions for medical patients recruited from health promotion clinics, and that these intentions predicted healthy eating behavior at a six-year follow-up (Conner et al, 2002).…”
Section: The Tpb and Dieting Or Healthy Eatingmentioning
confidence: 99%
“…That is, participants from that study who were characterized as food insecure as well as having higher intentions for healthy eating were more likely to have higher healthy food preparation scores (Suratkar et al, 2010). These results also mirror results from a study in Florida with a similar population of low-income African Americans, of older age, for whom intentions were found to be associated with higher consumption of fruits and vegetables (O’Neal et al, 2014). …”
Section: Discussionsupporting
confidence: 82%
“…Several studies that looked at fruit and vegetable consumption among African Americans found subjective norm to be important [34,35,36]. Britt et al [37] used the theory of planned behavior to examine the use of the human papillomavirus vaccine and found subjective norm to have an effect on behavioral intention when perceived behavioral control was the moderator.…”
Section: Discussionmentioning
confidence: 99%